Aplikasi Titip Online Produk UMKM Berbasis Android - Febrian Hidayat; Muhamad Sadali; Aris Sudianto (Infotek: Jurnal Informatika dan Teknologi, 2022)
UMKM have a big role in increasing economic growth in the region by increasing the number of UMKM in an area, it will show that buying and selling transaction activities will increase, not least in Selong District, East Lombok Regency. With the presence of the new UMKM, it is able to be a solution to reduce unemployment in East Lombok Regency, but in addition to being able to reduce the unemployment rate, it is very necessary to do how so that the products of UMKM  actors can be accessed more widely, because considering the community at this time very active in using smartphones. The purpose of this research is to create an application that will be able to accommodate all forms of products of UMKM actors in Selong District which of course with this application will be able to benefit both parties, namely the community as customers can search for their favorite UMKM products via smartphones, while for UMKM actors can promote their products more broadly so that they can increase the number of sales than before.